Geniposide Alleviates Glucocorticoid-Induced Inhibition of Osteogenic Differentiation in MC3T3-E1 Cells by ERK Pathway - Xie, Baocheng; Wu, Jiahuan; Li, Yongmei; Wu, Xuejun; Zeng, Zhanwei; Zhou, Chenhui; Xu, Daohua; Wu, Longhuo (Frontiers in Pharmacology, 2019)
Glucocorticoid (GC) therapy is the leading cause of secondary osteoporosis and the therapeutic and preventative drugs for GC-induced osteoporosis are limited. In this study, we investigated the protective effects of geniposide on dexamethasone (DEX)-induced osteogenic inhibition in MC3T3-E1 cells. The results showed that there was no obvious toxicity on MC3T3-E1 cells when geniposide was used at the doses ranging from 1 μM to 75 μM. In DEX-treated MC3T3-E1 cells, geniposide promoted the alkaline phosphatase (ALP) activity and the mineralization. In addition, geniposide also significantly increased the mRNA and protein expression of osteopontin (OPN), Runt-related transcription factor 2 (Runx2), and Osterix (Osx) in DEX-treated MC3T3-E1 cells. Furthermore, geniposide activated ERK pathway in DEX-treated MC3T3-E1 cells. The ERK activation inhibitor U0126 and glucagon-like peptide-1 (GLP-1) receptor antagonist exendin 9-39 abolished the geniposide-induced activation of ERK and inhibited the protective effect of geniposide. Taken together, our study revealed that geniposide alleviated GC-induced osteogenic suppression in MC3T3-E1 cells. The effect of geniposide was at least partially associated with activating ERK signaling pathway via GLP-1 receptor. Geniposide might be a potential therapeutic agent for GC-induced osteoporosis.